(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
In any economy extension of banking and post office services is closely associated with increase in monetization. In modern economic set-up growth of monetization in turn is expected to facilitate growth of economic activities through extension of markets. Hence level of monetization of any region may be considered as useful to understand developmental achievements of the concerned region. The present paper intends to enquire status of monetization of a region of the state of West Bengal of India. The region considered here is Jangal Mahal. Jangal Mahal is composed of three western districts of the state, Purulia, Bankura and Paschim Medinipur.